Modeling volcanic ash resuspension dynamics: the Eyjafjallajökull ash deposit case - Powell, Cameron Robert, 1989- (2018)
The eruption of Eyjafjallajökull in early 2010 led to an increase in the frequency of observed PM10 (particulate matter with diameter < 10 μm) resuspension events in the southern region of Iceland, attributed to the deposition of fresh volcanic tephra. Particulate matter under this diametric threshold is readily respirable by humans and livestock, and has been shown to cause adverse effects to human health and the agriculture and aviation industries. Improvements have been made to the processing of observational data from the time period of 23 May–2 July 2010, as well as to the scheme for calibration of the NAME Lagrangian dispersion model. A new method for calibration allowed for the derivation of a time-dependent scaling factor, representing the evolution of the source material as a function of time. The evolution of source material, due to various geomorphological and meteorological processes, affects its ability to be readily remobilized. Under the new calibration scheme, ash resuspension events in the immediate deposit proximity are captured 72% of the time, and those in the capital region to the southwest captured 57% of the time. This newly derived scaling factor indicates a rapid decline in volcanic ash resuspension following the end of an eruption event. The eruption signal dominates the record of observed PM10 levels in the immediate weeks following an event end, after which the normal dust resuspension record dust returns, with only minor influence from the remaining volcanic ash. Icelandic Research Fund Rannís grant #152587-051